2008
DOI: 10.1109/tns.2008.2001925
|View full text |Cite
|
Sign up to set email alerts
|

SEGR Study on Power MOSFETs: Multiple Impacts Assumption

Abstract: Expérience GANILInternational audienceThis paper presents experimental data showing heavy ions inducing gate degradation in power MOSFETs. In the experiments, backside and front-side irradiations are performed. During backside irradiation, the heavy ion ranges are tuned in such way to control whether they hit the gate or not. Gate-to-source current Igss ( ) is measured versus heavy ions (H.I.) fluence . Post-irradiation- gate-stress-test (PGST) allows measurement of gate breakdown voltage VBD( ) which is obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Other studies have shown that the dielectric breakdown was mainly affected by pre existing damage [33] and SEGR could also be triggered by ions crossing only the epitaxy without reaching the oxide [34]. Fig.…”
Section: Proposed Scenarios Of Single Event Effect 1) First Scenarmentioning
confidence: 87%
“…Other studies have shown that the dielectric breakdown was mainly affected by pre existing damage [33] and SEGR could also be triggered by ions crossing only the epitaxy without reaching the oxide [34]. Fig.…”
Section: Proposed Scenarios Of Single Event Effect 1) First Scenarmentioning
confidence: 87%
“…In case of SEGR, the minimum fluence cumulated before the event onset is about 10 3 ions.cm -2 . As described in a previous study [19], one can assume that these fluence limits belong to the "multiple impacts" regime. Complete analysis of the results will be provided in the final version of the paper.…”
Section: B Heavy Ion Irradiationmentioning
confidence: 99%
“…An abundant literature exists on this topic [1] however the mechanism that triggers the gate degradation or rupture is still under investigation and SEGR/SEB current test methods and test requirements [16]- [17] are still challenged. As of today, current issues address range or fluence requirements during ground-testing [19]- [20], relevance of the use of LET at the device surface for failure risk assessment purpose [18], [21], cumulative degradation hypothesis [20] rather than single ion impact effect, PIGST validity or relevance , etc… This is of main concern for the selection of devices dedicated to Space applications.…”
Section: Introductionmentioning
confidence: 99%
“…2,3) As with Si power MOSFETs, SiC MOSFETs are subject to single event effects in the space environment, most notably single event burnout (SEB) and single event gate rupture (SEGR). [4][5][6] SEB can result in catastrophic device failure, which has been a hot research area in recent years. [7][8][9][10][11] In comparison, SEGR has only recently begun to garner interest in recent years.…”
Section: Introductionmentioning
confidence: 99%